Regulation of Cell Death Induced by Acetic Acid in Yeasts - Chaves, Susana R.; Rego, António; Martins, Vítor M.; Santos-Pereira, Cátia; Sousa, Maria João; Côrte-Real, Manuela (Frontiers in Cell and Developmental Biology, 2021)
Acetic acid has long been considered a molecule of great interest in the yeast research field. It is mostly recognized as a by-product of alcoholic fermentation or as a product of the metabolism of acetic and lactic acid bacteria, as well as of lignocellulosic biomass pretreatment. High acetic acid levels are commonly associated with arrested fermentations or with utilization as vinegar in the food industry. Due to its obvious interest to industrial processes, research on the mechanisms underlying the impact of acetic acid in yeast cells has been increasing. In the past twenty years, a plethora of studies have addressed the intricate cascade of molecular events involved in cell death induced by acetic acid, which is now considered a model in the yeast regulated cell death field. As such, understanding how acetic acid modulates cellular functions brought about important knowledge on modulable targets not only in biotechnology but also in biomedicine. Here, we performed a comprehensive literature review to compile information from published studies performed with lethal concentrations of acetic acid, which shed light on regulated cell death mechanisms. We present an historical retrospective of research on this topic, first providing an overview of the cell death process induced by acetic acid, including functional and structural alterations, followed by an in-depth description of its pharmacological and genetic regulation. As the mechanistic understanding of regulated cell death is crucial both to design improved biomedical strategies and to develop more robust and resilient yeast strains for industrial applications, acetic acid-induced cell death remains a fruitful and open field of study.